Duration of admission for febrile convulsions?. Issue 12 (December 1985) - Green, A L; MacFaul, R
Abstract : Records of 199 children aged 5 to 71 months (mean 22.8) admitted after febrile convulsion were examined. Although 32 had recurrent convulsions (some before admission) none suffered a convulsion more than 24 hours after hospital admission.